Spectral binning of cervicovaginal fluid metabolites improves prediction of spontaneous preterm birth and Lactobacillus species dominance. Issue 4 (2nd December 2021) - Amabebe, Emmanuel; Reynolds, Steven; Anumba, Dilly O C
Abstract : Lay summary: Health-promoting bacteria (lactobacilli) exist in harmony with the vaginal environment. They are the predominant vaginal bacterial species during pregnancy. However, the possibility of infection and inappropriate immune response are linked with unprompted preterm delivery (PTD). Other invasive lactobacilli can alter the chemical environment of the vagina as they seek to promote their growth. This study measured the change in concentration of biochemical compounds and predominant bacterial species in vaginal fluid that are linked to PTD. The study recruited 300 healthy pregnant women who provided vaginal fluid samples during the second trimester. The women who harboured more of Lactobacillus jensenii over Lactobacillus crispatus (both reported as health-promoting bacteria) in their vaginal fluid had less lactate and glutamate and experienced more PTD. This suggests that lactate and glutamate levels in vaginal fluid may have clinical application in identifying which Lactobacillus species is most active. These chemical biomarkers could provide quick and accurate prediction of PTD risk in clinical settings.